Analisis Mantra Pengobatan "Tawar" Pada Masyarakat Dayak Limbai Kabupaten Melawi Kalimantan Barat (Kajian Semiotik) - Yelsi Fitri; Arni Arni; Ramadhan Kusuma Yuda (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2025)
This study aims to describe the meanings of icons, indices, and symbols in the “tawar” healing mantras of the Dayak Limbai community in Melawi Regency, West Kalimantan. This research employs a descriptive qualitative method with Charles Sanders Peirce’s semiotic approach. The data consist of ten healing mantras obtained through interviews and audio-recording techniques. The findings reveal 16 icons, 18 indices, and 18 symbols. Icons represent resemblance, indices indicate causal relationships, and symbols reflect cultural conventions and spiritual beliefs. These results indicate that the “tawar” mantra functions as traditional medicine as well as a form of local wisdom that can be integrated into Indonesian language learning.